2009
DOI: 10.1038/modpathol.2009.83
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear expression of dynamin-related protein 1 in lung adenocarcinomas

Abstract: Dynamin-related protein 1 (DRP1), an 80 kDa GTPase, is involved in mitochondrial fission and anticancer drugmediated cytotoxicity, which implicate an association with disease progression of cancer. In this study we investigated the prognostic value of DRP1 in lung adenocarcinomas. Using immunohistochemistry, we measured the expression of DRP1 in 227 patients with lung adenocarcinomas. Expression of DRP1 was confirmed by immunoblotting. The correlation between DRP1 expression and clinicopathological parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
114
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(124 citation statements)
references
References 39 publications
(61 reference statements)
9
114
0
1
Order By: Relevance
“…By showing that hypoxia-induced autophagic vesicles were encircled by DRP1 and the human homolog of yeast Rad23 protein A (hHR23A) as well, our previous data suggest that DRP1 and hHR23A may play a role in mammalian cell autophagy (17), based on the fact that hFis1 required DRP1 to carry out fission activities (37). Moreover, our current results provide a reasonable interpretation for the involvement of ATAD3A in autophagy and apoptosis, because ATAD3A may be able to provide energy for the movement of transport vesicles, transporting phospholipids and proteins from the ER, and mitochondria-associated membranes to the mitochondria.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…By showing that hypoxia-induced autophagic vesicles were encircled by DRP1 and the human homolog of yeast Rad23 protein A (hHR23A) as well, our previous data suggest that DRP1 and hHR23A may play a role in mammalian cell autophagy (17), based on the fact that hFis1 required DRP1 to carry out fission activities (37). Moreover, our current results provide a reasonable interpretation for the involvement of ATAD3A in autophagy and apoptosis, because ATAD3A may be able to provide energy for the movement of transport vesicles, transporting phospholipids and proteins from the ER, and mitochondria-associated membranes to the mitochondria.…”
Section: Discussionmentioning
confidence: 94%
“…Immunohistochemical staining was performed on paraffin-embedded tissues by an immunoperoxidase method as previously described (6,(14)(15)(16)(17)(18). Following removal of paraffin with xylene and alcohol, pathological sections were incubated with antibodies specific to ATAD3A (18), hepatocyte growth factor (HGF), HGF receptor (HGFR, or product of proto-oncogene c-met, c-MET), IL-8 (R&D Systems, Minneapolis, MN) or Ki-67 (zymed, San Francisco, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, hypoxic in vitro studies performed in other cell lines from the same tumor highlighted how hypoxic TME can lead to Mfn-1-dependent mitochondria elongation, with consequent increased organelle respiratory capacity and also increased resistance to apoptosis [55]. The resistance to apoptosis upon cisplatin treatment has been associated with i) lung adenocarcinoma patients with an unusual sequestration of Drp1 inside the nucleus (no more available to promote OMM hemifission) [56], ii) in tongue squamous cell carcinoma (TSCC) with the inhibition of Mff protein translation and mitochondria fission [57], and iii) apoptosis-resistant neuroblastoma cells with increased Opa-1 levels and fused mitochondria [58]. Further, deletion of the miR494-containing chromosomal fragment frequently occurs in different cancers [59] and, interestingly, restoring miR494 levels in renal carcinoma cells promotes cellular apoptosis in a process requiring Drp1-dependent mitochondrial fragmentation [60,61].…”
Section: Mitochondria-shaping Proteins In Apoptosismentioning
confidence: 99%
“…The synergistic action of XPC and hHR23B results in cytoresistance to chemotherapeutics and irradiation (23). Our recent report also showed that increase in the amount of nuclear dynamin-related protein 1 (DRP1) accompanied by nuclear accumulation of hHR23A was imperative for the increase of cisplatin resistance (25). Both hHR23A and hHR23B are involved in DNA repair and p53 stabilization.…”
Section: Discussionmentioning
confidence: 93%